Fulfilling Husband's Livelihood Obligations As A Migrant : Study in Sidorejo Village, Warungasem District, Batang Regency - Farah Ratu Octaviana (Asian Journal of Law and Humanity, 2023)
The husband is the leader of the household so that the husband as the head of the household has the obligation to provide physical and spiritual support. However, in reality, not all married people can fulfill their respective rights and obligations due to certain reasons. This is what happened in Sidorejo Village in families where the husband had to migrate, the husband had not been able to fully carry out his obligations in terms of providing support, both physical and mental support, so that the wife's rights had not been fulfilled. This neglect of providing a living results in various problems in their household life. This research aims to describe and analyze the fulfillment of husband's support obligations as a migrant as well as to explain and analyze the review of Islamic law regarding the fulfillment of husband's support obligations as a migrant in Sidorejo Village, Warungasem District, Batang Regency. This research is field research, where the researcher observes a phenomenon in a natural setting. The research approach used by researchers is a qualitative method. The data sources used are primary data sources and secondary data sources. Data collection techniques are interviews, observation and documentation. Data analysis in this research uses interactive model data analysis. The results of this research conclude that in terms of fulfilling the obligation of birth support (money), one of the migrant husbands in Sidorejo Village, Warungasem District, Batang Regency has carried out his obligations well, while the other two people have not been able to fulfill them. In terms of providing housing, everything has been fulfilled. In terms of good treatment, one of the husbands has done it well, while the other two people have not treated their wives well. Furthermore, regarding the issue of whether or not only one husband can guide his wife, the other two husbands have not been able to guide their wives well. Some migrant husbands in Sidorejo Village have fulfilled their husband's support obligations and are in accordance with the provisions of Islamic law and Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law, but there are also those who are not in accordance with the provisions of Islamic law and Law Number 1 of 1974. 1974 Concerning Marriage and the Compilation of Islamic Law.